CREATION OF GRADUATES' ENTREPRENEURIAL COMPETENCIES WITHIN THE EDUCATIONAL AREA OF BACCALAUREATE - Yuri B. Rubin (Moscow Polytechnic University, 2016)
The article describes different areas of professional activity that are chosen by graduates of bachelor degree programs in Entrepreneurship, typical directions of their business, types of appropriate business for them and main targets of successful studying. Also the article focuses on systems of professional competencies to be formed during learning process in Entrepreneurship education necessary for them to do business fruitfully on professional level and systems of entrepreneurial abilities which ought to be developed through teaching process. As a conclusion the author describes a practical model of learning process in Entrepreneurship for bachelor degree students.